PENGARUH KINERJA KEUANGAN, LEVERAGE, DAN CORPORATE GOVERNANCE TERHADAP SUSTAINABILITY REPORT - Reza Tahta Alviana; Murtanto Murtanto (EBID: Ekonomi Bisnis Digital, 2024)
The aim of this research is to present actual data on the impact of corporate governance, leverage, and financial performance on sustainability reports in manufacturing companies. Companies in the manufacturing sector that were listed between 2020 and 2022 on the Indonesia Stock Exchange (IDX) were the subject of this study. Secondary data from the financial statements of manufacturing businesses listed on the IDX is used in this study. In order to produce a sample of 225 samples, the sampling approach in this study employed the purposive sampling method with multiple specified criteria. Multiple linear regression analysis is the approach used for data analysis. It includes numerous tests, including classical assumption tests, hypothesis tests, and descriptive statistical tests. The SPSS (Statistical Product and Service Solution) version 26 application is used for the calculations of these tests.